Відтворення фразеологізованих концепт-реалій поеми «Енеїда» І. Котляревського в іншомовних перекладах (на основі назв страв) - Гаврилюк, Христина; Havrylyuk, Khrystyna (Східноєвропейський національний університет імені Лесі Українки, 2014)
Статтю присвячено аналізу способів відтворення фразеологізованих концепт-реалій (осьовий елемент – назва традиційної страви) у перекладах поеми «Енеїда» І. Котляревського. Встановлено закономірності відтво-рення первинної чи вторинної конотацій різними мовами залежно від їхньої історико-генеалогічної спорід-неності чи віддаленості./ The article represents the analysis of ways of rendering phraseological conceptual lexical realia (core element – names of traditional dishes) in foreign translations of the “Aeneid” by I. Kotliarevskyi. In a literary piece such structures tend to acquire a secondary phraseological connotation. Therefore, the specific lexicon loses its primary identity and should be viewed as part of a phraseological unit and reproduced accordingly. The analysis shows that genealogical proximity or remoteness has a crucial impact on the choice of a translation method. Close genetic ties between a source and target language contribute to a fuller representation of conceptual meaning in translation including one obtained through phraseologization which is due to existing semantic analogies. The major ways of preserving a secondary connotation of phraseological conceptual lexical realia are transliteration for close languages (Polish, Russian) and hypernymic renomination or descriptive paraphrasing for distant languages (English, German).
Rendering Phraseological Conceptual Realia of I. Kotliarevskyi’s Poem “Aeneid” Based on Traditional Names of Dishes in Foreign Translations
Гаврилюк Х. Відтворення фразеологізованих концепт-реалій поеми «Енеїда» І. Котляревського в іншомовних перекладах (на основі назв страв) / Христина Гаврилюк // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 13-19.
Keywords: поема «Енеїда»; фразеологізована концепт-реалія; концептуальне наповнення; вторинна конотація; спосіб перекладу; the poem “Aeneid”; phraseological conceptual lexical realia; conceptual meaning; secondary connotation; way of rendering